Mites and ticks of reptiles and amphibians in Brazil - Mendoza-Roldan, Jairo; Ribeiro, Stephany Rocha; Castilho-Onofrio, Valeria; Grazziotin, Felipe Gobbi; Rocha, Bruno; Ferreto-Fiorillo, Bruno; Pereira, Josivania Soares; Benelli, Giovanni; Otranto, Domenico; Barros-Battesti, Darci Moraes [UNESP] (Elsevier, 2020)
This study focuses on the parasitic associations of mites and ticks infesting reptiles and amphibians through a multifocal approach. Herein, reptiles (n= 3,596) and amphibians (n= 919) were examined to ensure representativeness of the Brazilian herpetofauna megadiversity. The overall prevalence was calculated to better understand which were the preferred hosts for each order of Acari (Trombidiformes, Mesostigmata and Ixodida), as well as to determine which orders frequently parasitize reptiles and amphibians in Brazil, and their host specificity. Infestation rates were calculated [prevalence, mean intensity (MI) and mean abundance (MA)] for each order and species, determining which mites and ticks are more likely to be found parasitizing the ectothermic tetrapod fauna. Parasitic niches and preferred locations were recorded to help identify specific places exploited by different Acari, and to determine the host-parasite adaptations, specificity, and relationships in terms of co-evolution. In total 4,515 reptiles and amphibians were examined, of which 170 specimens were infested by mites and ticks (overall prevalence of 3.8%). Trombidiformes mites were prevalent in lizards (55.3%), followed by Ixodida on snakes (24.7%). Mesostigmata mites were the less prevalent, being identified only on Squamata reptiles (4.3% on snakes, 2.4% on lizards). In amphibians, Ixodida ticks were the most prevalent (63.2%), followed by Trombidiformes (34.6%), and lastly Oribatida (2%). From the 13 species of Trombidiformes identified, Eutrombicula alfreddugesi (19.9%) was the most abundant in terms of number of host species and infested individuals. Specimens of Ixodida, yet more common, showed low preferred locations and different values of infestation rates. Co-infestations were recorded only on snakes. Lizard mites generally adhered to the ventral celomatic area (Pterygosomatidae), and some species to the pocket-like structures (Trombiculidae). Lizards, at variance from snakes, have adapted to endure high parasitic loads with minimum effects on their health. The high number of mites recorded in the digits of toads (Cycloramphus boraceiensis, Corythomantis greening, Cycloramphus dubius, Leptodactylus latrans, Melanophryniscus admirabilis) could lead to avascular necrosis. Frogs were often infested by Hannemania larvae, while Rhinella toads were likely to be infested by Amblyomma ticks. Of note, Rhinella major toad was found infested by an oribatid mite, implying first a new parasitic relationship. The effect of high parasitic loads on critically endangered species of anurans deserves further investigation. Our results add basic knowledge to host association of mites and ticks to Brazilian reptiles and amphibians, highlighting that routine ectoparasite examination is needed in cases of quarantine as well as when for managing reptiles and amphibians in captivity given the wide diversity of Acari on the Brazilian ectothermic tetrapod fauna.
Keywords: Amblyomma; Anura; co-evolution; ectothermic tetrapod fauna; host-parasite adaptation; Ixodida; Mesostigmata; Oribatida; Reptilia; Trombidiformes